Friday

April 18, 2014

April 18, 2014

Posted by **Anonymous** on Saturday, February 16, 2013 at 6:24am.

- ALEGBRA -
**Reiny**, Saturday, February 16, 2013 at 7:46amI assume your function is

f(x) = x^4 + x^3 - 8x^2 + 6x + 36

--- what about it?

If you want to factor it,

hint: f(-2) = 0 and f(-3) = 0

**Related Questions**

maths - the solution set for the following 1.X3+x2-6x-10=0 2.2x2-4x-4=0 3.x4-x3-...

Linear Algebra - Express the solutions of the following systems in terms of the ...

Math - Hi: I was wondering how I would even start to solve a problem like this. ...

math-check my work - Differentiate y=x(x4+5)3 d/dx = [x(x4+5)3] d/dx = [f(x)g(x...

Math - Use factorization to simplify the given expression in part (a). Then find...

ppaccademy Balangir math - p(x)+q(x) and p(x)-q(x),where p(x)=x3-2x2(square)-3 ...

ppaccademy Balangir math - p(x)+q(x) and p(x)-q(x),where p(x)=x3-2x2(square)-3 ...

Math - Is this equation right is it worked correctly x 1 ----- - -------- x2-4 ...

Math - Using the binomial theorem, Find the first three terms in the expansion ...

Math - Using the binomial theorem, Find the first three terms in the expansion ...